Laporan Penyelidikan Sarawak Memilih 2021: Kerjsama Penyelidikan Universiti Malaya - Astro Awani - Awang Azman, Awang Pawi; Novel, Lyndon; Lucy, Sebli; Juna, Liau; Suffian, Mansor; Stanley Bye, Kadam Kiai; Dick Lembang, Dugun (ejournal.um.edu.my, 2021)
Research Report Sarawak Decides 2021